2020
DOI: 10.3389/fcell.2020.545126
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Uses a Reversible Reprogramming of Mesenchymal Stromal Cells to Mediate Pro-tumorigenic Effects

Abstract: The role of mesenchymal stromal cells (MSCs) in the tumor microenvironment is well described. Available data support that MSCs display anticancer activities, and that their reprogramming by cancer cells in the tumor microenvironment induces their switch toward pro-tumorigenic activities. Here we discuss the recent evidence of pro-tumorigenic effects of stromal cells, in particular (i) MSC support to cancer cells through the metabolic reprogramming necessary to maintain their malignant behavior and stemness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 122 publications
(146 reference statements)
0
16
0
Order By: Relevance
“…Change the bone marrow microenvironment and inhibit the development of leukemia. Jafarzadeh et al, 2019;Nwabo Kamdje et al, 2020;Xia C. et al, 2020 Breast cancer Secrete exosomes to promote myeloid cells into M2-polarized breast cancer macrophages…”
Section: Cutaneous Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Change the bone marrow microenvironment and inhibit the development of leukemia. Jafarzadeh et al, 2019;Nwabo Kamdje et al, 2020;Xia C. et al, 2020 Breast cancer Secrete exosomes to promote myeloid cells into M2-polarized breast cancer macrophages…”
Section: Cutaneous Wound Healingmentioning
confidence: 99%
“…The reprogramming of macrophages by MSCs changes the bone marrow microenvironment and inhibits the development of leukemia (Xia C. et al, 2020). In the leukemia microenvironment, leukemia cell exosomes change the immune characteristics of MSCs and macrophages (Jafarzadeh et al, 2019;Nwabo Kamdje et al, 2020). In addition, MSCs can reprogram macrophages into M2 macrophages with phagocytosis functions and can reduce the secretion of proinflammatory factors to control the tumor microenvironmental immunity (Wolfe et al, 2016;Francois et al, 2019;Wang et al, 2019).…”
Section: Hematopoietic Microenvironmentmentioning
confidence: 99%
“…Possessing important roles in tumor progression, the proportion of CA-MSCs has been demonstrated to dynamically increase throughout the distinct stages of tumor (64). Although tumor cells alone can partly "educate" the naïve MSCs to change their phenotypes and functions, the surrounding microenvironment have also emerged to play a dominant role in the malignant transition of naïve MSCs into tumoral MSCs (65,66). In various solid tumors, the TME together with tumor cells have been demonstrated to participate in promoting MSC transition into CA-MSCs (67).…”
Section: Conversion Of Naïve Mscs Into Ca-mscs By the Tmementioning
confidence: 99%
“…Several studies have shown that BM or adipose MSCs [called adipose-derived stromal cells (ADSCs)] have a particular tropism for primary tumors (81,82). MSCs can either favor or inhibit primary tumor growth and metastasis (78,81,(83)(84)(85)s. Recent evidence has also shown that the nature of tumor cells, in particular their low or high aggressiveness, dictates the type of interactions with MSCs and notably the production of multiple chemokines and prostaglandin E2 upon release of IL-1b by tumor cells.…”
Section: Niche Cytokines and Chemokinesmentioning
confidence: 99%